2007
DOI: 10.1002/cncr.22844
|View full text |Cite
|
Sign up to set email alerts
|

A study of the volatile organic compounds exhaled by lung cancer cells in vitro for breath diagnosis

Abstract: Bench‐scale tests to study the effect of water mist on burning solid poly(vinyl chloride) (PVC) were carried out with a cone calorimeter. Water mist was discharged from a small nozzle under two operating pressures, 0.4 and 0.7 MPa. The corresponding water flow rates were 103.5 and 134 mL/min, respectively. The cone angle of the discharged water spray was 90°, and the volume mean diameter of the mist was about 90 μm. The results were useful in understanding the effects of discharging water mist to suppress the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
150
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(153 citation statements)
references
References 28 publications
1
150
1
1
Order By: Relevance
“…20,21 Orna et al performed exhaled breath analyses of patients with different lung cancer pathologies and found that the composition of exhaled VOCs was different among these patients; in particular, the concentrations of the three compounds of 2-ethyl-1-hexanol, 1,3-dimethyl-benzene, and 1,3-bis(1,1-dimethylethyl)-benzene were significantly higher in patients with adenocarcinoma than in patients with squamous cell carcinoma. 22 Chen et al 23 examined four types of lung cancer, including adenocarcinoma, squamous cell carcinoma, bronchial carcinoid tumor, and non-small-cell lung cancer, and determined that different VOCs are exhaled by patients with different lung cancer types. Because exhaled metabolites are derived from metabolites in the blood that are released into the air via the pulmonary circulation, pathological differences among patients may also correlate with differences in the metabolites in patients' blood.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Orna et al performed exhaled breath analyses of patients with different lung cancer pathologies and found that the composition of exhaled VOCs was different among these patients; in particular, the concentrations of the three compounds of 2-ethyl-1-hexanol, 1,3-dimethyl-benzene, and 1,3-bis(1,1-dimethylethyl)-benzene were significantly higher in patients with adenocarcinoma than in patients with squamous cell carcinoma. 22 Chen et al 23 examined four types of lung cancer, including adenocarcinoma, squamous cell carcinoma, bronchial carcinoid tumor, and non-small-cell lung cancer, and determined that different VOCs are exhaled by patients with different lung cancer types. Because exhaled metabolites are derived from metabolites in the blood that are released into the air via the pulmonary circulation, pathological differences among patients may also correlate with differences in the metabolites in patients' blood.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 2,2,4,6,6-pentamethylheptane and decane were identified and compared by Poli et al [68] in exhaled breath of patients with non-small lung cancer (NSLC), chronic obstructive pulmonary disease (COPD), smokers and controls and their concentrations were higher for NSLC, COPD and smokers when compared to controls. Dodecane has been proposed as lung cancer markers [69,70].…”
Section: Multivariate Analysis In the Establishment Of Asthma "Breathmentioning
confidence: 99%
“…For that reason, the FID detector is very often used in breath analysis. The GC−FID sensor has been successfully applied to detect acetone, pentane, isoprene, hexanal and other volatile organic com− pounds [10] as well as for observation of lung cancer cells and bacterial cultures [11,12].…”
Section: Non-optical Methods Of Breath Analysismentioning
confidence: 99%